2004
DOI: 10.1177/154405910408300605
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro Permeability of One-step Self-etch Adhesives

Abstract: Adhesive dentistry should effectively restore the peripheral seal of dentin after enamel removal. We hypothesize that non-rinsing, simplified, one-step self-etch adhesives are effective for minimizing dentin permeability after tooth preparation procedures. Crown preparations in vital human teeth were sealed with Adper Prompt, Xeno III, iBond, or One-Up Bond F. Epoxy resin replicas were produced from polyvinyl siloxane impressions for SEM examination. Dentin surfaces from extracted human teeth were bonded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
101
0
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 16 publications
3
101
0
14
Order By: Relevance
“…[5][6][7] The adverse effect of one-step self-etch adhesive hydrophilicity on bonding to dentin has been reported. [8][9][10][11][12] In vitro dentin bond strength tests indicate that the hydrophilicity of one-step self-etch adhesives is a contributive cause for reduced short-term 13 and medium-term values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] The adverse effect of one-step self-etch adhesive hydrophilicity on bonding to dentin has been reported. [8][9][10][11][12] In vitro dentin bond strength tests indicate that the hydrophilicity of one-step self-etch adhesives is a contributive cause for reduced short-term 13 and medium-term values.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical performance of one-step self-etch adhesive systems has been shown to have inferior clinical success rates when compared with two-step or three-step self-etch and etch-and-rinse systems. 16 In vivo evidence of water blistering within and protruding from the one-step self-etch adhesive layer has also been documented, 8,17 especially for HEMA-containing formulations. The water diffusion channels are made visible in cross-sectional images by ammonical silver nitrate tracing, 18 revealing geometries that imply the outward fluid flow from a moist substrate and dentinal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] An effective, long-lasting tooth-restoration bond is desirable, because it would prevent microleakage and, consequently, inhibit the development of secondary caries. This would allow for conservative cavity preparations with less need for mechanical retention.…”
Section: Introductionmentioning
confidence: 99%
“…Simplified adhesive resins have been shown to act as semi-permeable membranes permitting water penetration through the resin-dentin interfaces [13,14], resulting in reduced bond durability [15][16][17][18]. Studies have reported that the permeability phenomenon could be attributed to the presence of incompletely polymerized acidic monomers within the hybrid layer or dentinal tubules [13,19,20].…”
Section: Introductionmentioning
confidence: 99%